2018
DOI: 10.1111/phpp.12396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet light on mood, depressive disorders and well‐being

Abstract: Summary Background Human and animal studies have shown that exposure to ultraviolet light can incite a chain of endocrine, immunologic, and neurohumoral reactions that might affect mood. This review focuses on the evidence from clinical trials and observational studies on the effect of ultraviolet light on mood, depressive disorders, and well‐being. Methods A search was made in PubMed, Embase, Web of Science, Cochrane, Psychinfo, CINAHL, Academic Search Premier and Science Direct, and the references of key pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Melatonin inhibits secretion [65] Excessive UV-B can cause erythema or DNA damage [71] Reduce the risk of cardiovascular disease [7,8,68,72] UVA-1 induces pigmentation of IV-VI type Improve psychological problems such as depression and seasonal mood [6,48,73,74] Uncomfortable glare problem [2,75] Reduce the risk of colorectal cancer [69] Excessive heat will cause an increase indoor electrical energy consumption [16] Reduce the incidence of diabetes [72] 2.…”
Section: The Benefits Of Daylight the Disadvantages Of Daylightmentioning
confidence: 99%
“…Melatonin inhibits secretion [65] Excessive UV-B can cause erythema or DNA damage [71] Reduce the risk of cardiovascular disease [7,8,68,72] UVA-1 induces pigmentation of IV-VI type Improve psychological problems such as depression and seasonal mood [6,48,73,74] Uncomfortable glare problem [2,75] Reduce the risk of colorectal cancer [69] Excessive heat will cause an increase indoor electrical energy consumption [16] Reduce the incidence of diabetes [72] 2.…”
Section: The Benefits Of Daylight the Disadvantages Of Daylightmentioning
confidence: 99%
“…5,6 Too little sunlight leads to deficiency in vitamin D and can precipitate mood disorders in predisposed individuals. 7 Latitude gradients are found for several autoimmune diseases, such as multiple sclerosis and type I diabetes, with increasing prevalence found with higher latitudes suggesting a role for the interplay between UVR and vitamin D status. 8 Furthermore, phototherapy is used to treat a number of skin disorders including psoriasis, atopic dermatitis, polymorphic light eruption, vitiligo, alopecia areata and lichen planus, among others, suggesting that the immunomodulatory effects of UVR regulate some autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Too much sunlight leads to sunburn and mutations in DNA that promote skin tumourigenesis 5,6 . Too little sunlight leads to deficiency in vitamin D and can precipitate mood disorders in predisposed individuals 7 . Latitude gradients are found for several autoimmune diseases, such as multiple sclerosis and type I diabetes, with increasing prevalence found with higher latitudes suggesting a role for the interplay between UVR and vitamin D status 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review exploring the evidence obtained from clinical studies on the effect of UV light or light therapy on mood and depressive disorders included seven studies. 9 In only one study, patients were exposed to broadband UVB (BBUVB). 10 Of the seven studies, six demonstrated a positive effect of UV light on mood.…”
Section: Introductionmentioning
confidence: 99%